Serotonin Transporter Binding in Bipolar Disorder Assessed using [ 11C]DASB and Positron Emission Tomography - Cannon, Dara M.; Ichise, Masanori; Fromm, Stephen J.; Nugent, Allison C.; Rollis, Denise; Gandhi, Shilpa K.; Klaver, Jacqueline M.; Charney, Dennis S.; Manji, Husseini K.; Drevets, Wayne C. (Biological psychiatry (1969), 2006)
Evidence from neuroimaging post-mortem, and genetic studies suggests that bipolar disorder (BD) is associated with abnormalities of the serotonin-transporter (5-HTT) system. Because of various limitations of these studies, however, it has remained unclear whether 5-HTT binding is abnormal in unmedicated BD-subjects. This study used PET and [ 11C]DASB, a radioligand that afforded higher sensitivity and specificity for the 5-HTT than previously available radioligands, to compare 5-HTT binding between BD and control subjects. The 5-HTT binding-potential (BP) was assessed in 18 currently-depressed, unmedicated BD-subjects and 37 healthy controls using PET and [ 11C]DASB. In BD, the mean 5-HTT BP was increased in thalamus, dorsal cingulate cortex (DCC), medial prefrontal cortex and insula and decreased in the brainstem at the level of the pontine raphe-nuclei. Anxiety ratings correlated positively with 5-HTT BP in insula and DCC, and BP in these regions was higher in subjects manifesting pathological obsessions and compulsions relative to BD-subjects lacking such symptoms. Subjects with a history of suicide attempts showed reduced 5-HTT binding in the midbrain and increased binding in anterior cingulate cortex versus controls and to BD-subjects without attempts. This is the first study to report abnormalities in 5-HTT binding in unmedicated BD-subjects. The direction of abnormality in the brainstem was opposite to that found in the cortex, thalamus, and striatum. Elevated 5-HTT binding in the cortex may be related to anxiety symptoms and syndromes associated with BD.